Anti rolling back material design used for hill station vehicle. (2021) - Nagalakshmi, R.; Johnsi, J.; Nandini, K.; Surendran, T.
Abstract: The motors advancements in cars, truck, is the foremost method of transportation nowadays. Using cars and other transport vehicles to drive through the hill places is tough. To evade chances of accident and opposite rollover in reverse of the car while it is in the halt position and start in the hill roads needs excellence in using clutch, brake and speeding up and that is difficult for drivers who have less experience. The system proposed here is done by the Arduino design allows the driver to handgrip the car without difficulty in the hill stations, and eludes unnecessary accidents. The detection and sensing is done automatically for the clutch, accelerator. The mode selection switch positions used in the system and the brake system are functioned immediately to get escape from any impact. The emergency system lets the vehicle to put on brakes in close chance meeting with further obstacles.